High‐efficiency two‐switch tri‐state buck–boost power factor correction converter with fast dynamic response and low‐inductor current ripple. Issue 8 (1st September 2013) - He, Mingzhi; Zhang, Fei; Xu, Jianping; Yang, Ping; Yan, Tiesheng
Abstract : Two‐switch tri‐state buck–boost power factor correction (PFC) converter operating in pseudo‐continuous conduction mode is proposed and analysed in this study. Different from tri‐state boost PFC converter, the proposed two‐switch tri‐state buck–boost PFC converter does not need additional power switch to provide the additional degree of control freedom. Therefore it does not increase the complexity and affect the power conversion efficiency of the PFC converter as in the case of tri‐state boost PFC converter. For the proposed two‐switch tri‐state buck–boost PFC converter, the current control loop and voltage control loop are decoupled, a simple voltage control loop with faster dynamic response can be designed to realise output voltage regulation and the additional degree of control freedom introduced by inductor current freewheeling stage helps to achieve unity power factor control. The operation principle, the input current, the inductor current ripple, the switch component stress and the small‐signal characteristics of the proposed two‐switch tri‐state buck–boost PFC converter are analysed. The simulation and experimental results show that the proposed two‐switch tri‐state buck–boost PFC converter benefits with fast dynamic response, high‐efficiency and low‐inductor current ripple over single‐switch buck–boost PFC converter or two‐switch buck–boost PFC converter operating in continuous conduction mode and discontinuous conduction mode.